O clima da cidade de Caucaia-CE sob uma perspectiva termodinâmica - Oliveira, Jorge Ricardo Felix de (2014)
The relationship of the dynamics of the lower atmosphere to urban settlements becomes influence the thermal exchanges between the Sun and the Earth producing transformations of energy often perceived negatively. In this sense we propose a study of urban climate, a thermodynamic perspective, the municipal headquarters of Caucaia, Ceará, located in the Metropolitan Region of Fortaleza. In order to check the thermal differences in two periods of Ceará rainy season and the influence of land use and occupation in the climatic attributes of different spaces intraurbanos The survey basically follows the theoretical and conceptual proposal of the Urban Climate System-SCU, with the thermodynamic subsystem (perception channel thermal comfort) of MONTEIRO (1976, 2003). In association with the analysis of active weather systems, measurements were performed with the mobile and fixed transect mini-shelters in a 48hrs profile in representative days of January and May 2014. Furthermore, it was ascertained through satellite imaging Landsat 8 ( Band 10) behaves surface temperature city. One can show that the weather systems influence the characteristics of climatic attributes considered. It was found that temperatures of greater value surface were found in the central area of the city, in an industry characterized by the absence of vegetation, with fiber cement roofs. The measurements with the mini-shelters installed in the yards of homes, showed the influence of building materials in conditioning temperatures and humidities. In the experiments with the mobile transects, in general, we find a small variation of the temperatures and humidities of air, ranging between 1.3 ° C and 5% in summer; and 2,1ºC with 13% in autumn, and the center the location with the highest values.